Emerging trends of traumatic brain injury in Western Uttar Pradesh, India: diagnosis and rehabilitation - Arfat, Mohd.; Verma, A. P.; Shukla, Arvind; Mittal, Kailash K. (International Journal of Research in Medical Sciences, 2019)
Background: To study the various advance technology for the diagnosis of Traumatic Brain Injury (TBI) and find out Emerging trends occur in TBI (Traumatic Brain Injury) patients. Methods: The present study was conducted with 500 patients, age between 02 year to 70 years mean age (36 Years) presenting to emergency department of Uttar Pradesh University of Medical Sciences, Saifai, Etawah, with a history of acute head trauma from January 2016 to December 2018. All patients were examined using 64 slices MDCT and 1.5T MRI Scanner also. Results: Traumatic brain injury caused by various reasons like 62.1% road traffic accidents (RTA) and 25.1% fall from height (FFH) being and 11.83% Assault/hit by hard object and 0.88% are gunshot injury. Loss of consciousness was the most common complaint of the 59.1% TBI patients followed by 17.75% Vomiting and headache, 11.83% facial injury and 11.24% scalp injury. All TBI patients were diagnosed by MDCT 64 Slices Somatom Sensation Scanner who was observed 41.42% skull fractures, 29.28% extra dural hematoma, 27.21% sub dural hematoma, 23.96% sub archnoid haemorrhage, 13% intra cerebral hematoma, 30.17% brain contusions and 24.26% diffuse cerebral edema. Conclusions: Road traffic accidents remain the leading cause of trauma in our country. MRI and MDCT are well recognized method to know the extent and various types of hemorrhages and skull fractures in TBI patients. The present study data is indicated 62.1% majority of TBI patients are suffered by Road traffic accidents mainly young males with alcoholism.